PREVALENCE OF VANCOMYCIN RESISTANT STAPHYLOCOCCUS AUREUS ISOLATED FROM DAIRY PRODUCTS IN KURDISTAN REGION-IRAQ - KHUDHER, HAVAL ABDULLAH; ALZUBAIDY, ZAINAB M.; ABDO, JASEM M. (Journal of Duhok University, 2023)
The context highlights the importance of Staphylococcus aureus as a potential cause of foodborne illnesses, its capacity to become resistant to antibiotics such as vancomycin, and the possible dangers posed by dairy products contaminated with VRSA to public wellbeing. The main aim of the research is to gauge the prevalence of VRSA in dairy items within the Kurdistan Region, revealing potential risks to both food security and the well-being of consumers. So, in this study, the resistance of 69 of S. aureus bacteria isolated from 300 Kurdish locally cheese, hard cheese, soft cheese, yogurt, samples to six types of antibiotics (clindamycin, tetracycline, Rifampicin, erythromycin, vancomycin and Ampicillin) were evaluated. The 69 isolates were identified by Vitec system2, also confirmed by specific primer of 16SrRNA gene, those isolated both results are the same. Antimicrobial resistance of strains to six antibiotics was determined by using Vitec system2, and disc diffusion method. The antibacterial resistance among all the isolated were detected against Erythromycin 53(77%), clindamycin 65(94), vancomycin 25(36%), tetracycline 62(90%), Rifampicin 61(88%), ampicillin 69(100%). Antibiotic resistance genes were studied by polymer chain reaction and the following genes were detected, in totally 19 isolated present Van (A), and 16 isolated present Van(B) from 25 isolated they were resistance to vancomycin as antibacterial